2018
DOI: 10.1136/tobaccocontrol-2018-054324
|View full text |Cite
|
Sign up to set email alerts
|

Light and mild redux: heated tobacco products’ reduced exposure claims are likely to be misunderstood as reduced risk claims

Abstract: Introduction Heated tobacco products (HTPs) are being marketed in several countries around the world with claims that they are less harmful than combusted cigarettes, based on assertions that they expose users to lower levels of toxicants. In the USA, Philip Morris International (PMI) has submitted an application to the Food and Drug Administration (FDA) in 2016 seeking authorisation to market its HTPs, IQOS, with reduced risk and reduced exposure claims. Methods We examined the PMI’s Perception and Behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…HTP users were significantly more likely to believe that HTPs are less harmful than cigarettes compared to non-HTP users, with this belief being more prominent among frequent users. Smokers who have been exposed to HTP marketing appear to hold beliefs that are consistent with these advertising messages in Japan [36]. Even though existing scientific data show less exposure to toxic substances from HTPs than from cigarettes [7,12,13,17], advertising HTPs as reduced-risk products should be prohibited until the scientific community comes to a consensus about the ultimate effect of HTP use on health.…”
Section: Resultsmentioning
confidence: 99%
“…HTP users were significantly more likely to believe that HTPs are less harmful than cigarettes compared to non-HTP users, with this belief being more prominent among frequent users. Smokers who have been exposed to HTP marketing appear to hold beliefs that are consistent with these advertising messages in Japan [36]. Even though existing scientific data show less exposure to toxic substances from HTPs than from cigarettes [7,12,13,17], advertising HTPs as reduced-risk products should be prohibited until the scientific community comes to a consensus about the ultimate effect of HTP use on health.…”
Section: Resultsmentioning
confidence: 99%
“…Most research on consumer responses to IQOS has been conducted by PMI 22–25. Independent survey research found that IQOS is perceived as less harmful than smoking 26–28.…”
Section: Introductionmentioning
confidence: 99%
“…Marketing of these products, and claims being made about them, need to be regulated 7 , 27 . In 2016 in Japan, the appearance of IQOS in a popular television programme was followed by a rapid increase in IQOS use, highlighting the need to regulate HTP marketing and use 28 .…”
Section: Introductionmentioning
confidence: 99%